Effects of Tire Crumb Rubber and Steel Fiber on Punching Shear Behavior of Two-way Alkali-activated Concrete Flat Slabs - Eren, Necip Altay; Çevik, Abdulkadir (Periodica Polytechnica Civil Engineering, 2024)
As a result of the rapid increase in the demand for transportation vehicles recently, the accumulation of waste tires causes environmental problems. One of the methods that can contribute to the reduction of this environmental problem is the recycling of waste tires as a construction material in aggregate form. This research investigated the impacts of waste tire crumb rubber with/out steel fiber (SF) on the two-way punching-shear behavior alkali-activated concrete (AAC) flat slabs and performed center point load tests. In the study, one-type of SF and two kinds of scrap tire waste i.e., crumb rubber (CR) and tire particles, were used on the producing of rubberized AAC slabs obtained by 100% as binder made of ground-granulated blast furnace slag (GGBFS). Also, while both fine crumb rubber (FCR) and coarse crumb rubber (CCR) were used together in the AAC slabs, tire crumb rubber (TCR) was used alone at the same proportion. Additionally, the fine aggregate was substituted with 10% and 15% FCR and CCR, and coarse aggregate was substituted with TCR in the same proportions. Additionally, AAC slabs with recycled tire rubber (RTR) were produced as fibrous and non-fibrous using 1% by volume hook-end SF. In total, nine AAC slabs with sizes of 50 x 50 x 6 cm3 were manufactured for the study. Experimental data showed that the inclusion of RTR only slightly reduced the punching shear strength of AAC slabs and the punching shear strength of the slabs increased when SF was added to the mixtures containing RTR.